Intact cell MALDI mass spectrometry as a tool to screen drugs in vivo for regulation of protein expression - Kulkarni, Mahesh J.; Vinod, V. P.; Umashankar, P. K.; Patole, M.; Rao, M. (Molecular & Cellular Proteomics, 2006)

Identification of ripening specific proteins in tomato by intact tissue MALDI-TOF-MS. - Korwar, Arvind M.; Santhakumari, B.; Kulkarni, Mahesh J. (Electronic Journal of Food and Plants Chemistry, 2008)

Interaction of recombinant CanPIs with helicoverpa armigera gut proteases reveals their processing patterns, stability and efficiency - Mishra, Manasi; Tamhane, Vaijayanti A.; Khandelwal, Neha; Kulkarni, Mahesh J.; Gupta, Vidya S.; Giri, Ashok P. (Proteomics, 2010)
Six diverse representative Capsicum annuum (common name: hot pepper; Solanaceae) protease inhibitor genes, viz CanPI-5, -7, -13, -15, -19, and 22 comprising 1-4 inhibitory repeat domains (IRDs), were cloned and expressed in Pichia pastoris. The recombinant proteins were evaluated for their interactions with bovine trypsin, chymotrypsin, and Helicoverpa armigera gut proteases (HGP) using electrophoretic (native and denaturing) and mass spectrometric (MALDI-TOF-MS in combination with intensity fading assays) techniques. These techniques allow qualitative and semiquantitative analysis of multiple and processed IRDs of purified recombinant Capsicum annuum proteinase inhibitor (rCanPI) proteins. rCanPIs showed over 90% trypsin inhibition, varying chymotrypsin inhibition depending on the number of respective IRDs and over 60% inhibition of total HGP. rCanPI-15 that has only one IRD showed exceptionally low inhibition of these proteases. Interaction studies of rCanPIs with proteases using intensity fading-MALDI-TOF-MS revealed gradual processing of multi-IRD rCanPIs into single IRD forms by the action of HGP at the linker region, unlike their interactions with trypsin and chymotrypsin. Intensity fading-MALDI-TOF-MS assay showed that CanPI-13 and -15, possessing single IRD and expressed predominantly in stem tissue are degraded by HGP; indicating their function other than defense. In vitro and in vivo studies on rCanPI-5 and -7 showed maximum inhibition of HGP isoforms and their processed IRDs were also found to be stable in the presence of HGP. Even single amino acid variations in IRDs were found to change the HGP specificity like in the case of HGP-8 inhibited only by IRD-12. The presence of active PI in insect gut might be responsible for changed HGP profile. rCanPI-5 and -7 enhanced HGP-7, reduced HGP-4, -5, -10 expression and new protease isoforms were induced. These results signify isoform complexity in plant PIs and insect proteases.
Keywords: CanPI; H. armigera gut proteases; Intensity fading MALDI-TOF-MS; Pin-II; Plant proteomics; Plant-insect interaction

Immune response to chemically modified proteome - Bhat, Shweta; Mary, Sheon; Banarjee, Reema; Giri, Ashok P.; Kulkarni, Mahesh J. (Proteomics Clinical Applications, 2014)
Both enzymatic and nonenzymatic PTMs of proteins involve chemical modifications. Some of these modifications are prerequisite for the normal functioning of cell, while other chemical modifications render the proteins as neo-self antigens, which are recognized as non-self leading to aberrant cellular and humoral immune responses. However, these modifications could be a secondary effect of autoimmune diseases, as in the case of type I diabetes, hyperglycemia leads to protein glycation. The enigma of chemical modifications and immune response is akin to the chick-and-egg paradox. Nevertheless, chemical modifications regulate immune response. In some of the well-known autoimmune diseases such as rheumatoid arthritis, systemic lupus erythematosus, and multiple sclerosis, chemically modified proteins act as autoantigens forming immune complexes. In some instances, chemical modifications are also involved in regulating immune response during pathogen infection. Further, the usefulness of proteomic analysis of immune complexes is briefly discussed.
Keywords: Autoantibody; Autoimmune diseases; Immune complex; Immunoproteomics; PTMs

Insecticidal potential of defense metabolites from ocimum kilimandscharicum against helicoverpa armigera - Singh, Priyanka; Jayaramaiah, Ramesha H.; Sarate, Priya; Thulasiram, Hirekodathakallu V.; Kulkarni, Mahesh J.; Giri, Ashok P. (Plos One, 2014)
Genus Ocimum contains a reservoir of diverse secondary metabolites, which are known for their defense and medicinal value. However, the defense-related metabolites from this genus have not been studied in depth. To gain deeper insight into inducible defense metabolites, we examined the overall biochemical and metabolic changes in Ocimum kilimandscharicum that occurred in response to the feeding of Helicoverpa armigera larvae. Metabolic analysis revealed that the primary and secondary metabolism of local and systemic tissues in O. kilimandscharicum was severely affected following larval infestation. Moreover, levels of specific secondary metabolites like camphor, limonene and beta-caryophyllene (known to be involved in defense) significantly increased in leaves upon insect attack. Choice assays conducted by exposing H. armigera larvae on O. kilimandscharicum and tomato leaves, demonstrated that O. kilimandscharicum significantly deters larval feeding. Further, when larvae were fed on O. kilimandscharicum leaves, average body weight decreased and mortality the larvae increased. Larvae fed on artificial diet supplemented with O. kilimandscharicum leaf extract, camphor, limonene and beta-caryophyllene showed growth retardation, increased mortality rates and pupal deformities. Digestive enzymes of H. armigera - namely, amylase, protease and lipase- showed variable patterns after feeding on O. kilimandscharicum, which implies striving of the larvae to attain required nutrition for growth, development and metamorphosis. Evidently, selected metabolites from O. kilimandscharicum possess significant insecticidal activity.

Investigation of antiglycation activity of isoprenaline - Kolekar, Yogesh M.; Vannuruswamy, Garikapati; Bansode, Sneha B.; Santhakumari, B.; Thulasiram, Hirekodathakallu V.; Kulkarni, Mahesh J. (RSC Advances, 2015)
Advanced glycation end products (AGEs) are implicated in pathogenesis of diabetes and its complications. In this study, we report the ability of isoprenaline to inhibit the AGE modification of protein by fluorescence spectroscopy and western blotting. Isoprenaline was more effective in inhibiting AGE modification than aminoguanidine, a well known glycation inhibitor. Further, we show that isoprenaline inhibits at Amadori product formation during glycation reaction by various techniques such as MALDI-TOF-MS, LC-MS/MS, and fructosamine assay. Mass spectrometric analysis of the glycation reaction mixture incubated with isoprenaline suggested that it forms adducts with glucose and thus inhibits glycation. The finding of the additional property of isoprenaline of inhibiting glycation suggests that it is a potential candidate for drug repositioning for the treatment of diabetes and its complications, as it is an FDA approved drug.

Investigation of phosphoproteome in RAGE signaling - Batkulwar, Kedar B.; Bansode, Sneha B.; Patil, Gouri V.; Godbole, Rashmi K.; Kazi, Rubina S.; Chinnathambi, Subashchandrabose; Shanmugam, Dhanasekaran; Kulkarni, Mahesh J. (Proteomics, 2015)
The receptor for advanced glycation end products (RAGE) is one of the most important proteins implicated in diabetes, cardiovascular diseases, neurodegenerative diseases, and cancer. It is a pattern recognition receptor by virtue of its ability to interact with multiple ligands, RAGE activates several signal transduction pathways through involvement of various kinases that phosphorylate their respective substrates. Only few substrates have been known to be phosphorylated in response to activation by RAGE (e.g., nuclear factor kappa B); however, it is possible that these kinases can phosphorylate multiple substrates depending upon their expression and localization, leading to altered cellular responses in different cell types and conditions. One such example is, glycogen synthase kinase 3 beta which is known to phosphorylate glycogen synthase, acts downstream to RAGE, and hyperphosphorylates microtubule-associated protein tau causing neuronal damage. Thus, it is important to understand the role of various RAGE-activated kinases and their substrates. Therefore, we have reviewed here the details of RAGE-activated kinases in response to different ligands and their respective phosphoproteome. Furthermore, we discuss the analysis of the data mined for known substrates of these kinases from the PhosphoSitePlus (http://www.phosphosite.org) database, and the role of some of the important substrates involved in cancer, diabetes, cardiovascular diseases, and neurodegenerative diseases. In summary, this review provides information on RAGE-activated kinases and their phosphoproteome, which will be helpful in understanding the possible role of RAGE and its ligands in progression of diseases.
Keywords: Cell biology; Disease; Glycation; Kinase; Phosphoproteome; RAGE

Investigation of the captopril-insulin interaction by mass spectrometry and computational approaches reveals that captopril induces structural changes in insulin - Ghosh, Amrita; Pawar, Aiswarya B.; Chirmade, Tejas; Jathar, Swaraj M.; Bhambure, Rahul; Sengupta, Durba; Giri, Ashok P.; Kulkarni, Mahesh J. (ACS Omega, 2022)
ABSTRACT: Post-translational modifications remarkably regulate proteins' biological function. Small molecules such as reactive thiols, metabolites, and drugs may covalently modify the proteins and cause structural changes. This study reports the covalent modification and noncovalent interaction of insulin and captopril, an FDA-approved antihypertensive drug, through mass spectrometric and computation-based approaches. Mass spectrometric analysis shows that captopril modifies intact insulin, reduces it into its ``A'' and ``B'' chains, and covalently modifies them by forming adducts. Since captopril has a reactive thiol group, it might reduce the insulin dimer or modify it by reacting with cysteine residues. This was proven with dithiothreitol treatment, which reduced the abundance of captopril adducts of insulin A and B chains and intact Insulin. Liquid chromatography tandem mass spectrometric analysis identified the modification of a total of four cysteine residues, two in each of the A and B chains of insulin. These modifications were identified to be Cys6 and Cys7 of the A chain and Cys7 and Cys19 of the B chain. Mass spectrometric analysis indicated that captopril may simultaneously modify the cysteine residues of intact insulin or its subunits A and B chains. Biophysical studies involving light scattering and thioflavin T assay suggested that the binding of captopril to the protein leads to the formation of aggregates. Docking and molecular dynamics studies provided insights into the noncovalent interactions and associated structural changes in insulin. This work is a maiden attempt to understand the detailed molecular interactions between captopril and insulin. These findings suggest that further investigations are required to understand the long-term effect of drugs like captopril.